The Effect of the Rotation Model on Blended Learning Stations on Mathematics Achievement among Third-Grade Middle School Female Students (Journal Of Educational and Psychological Researches, 2024)
The current research aims to identify the effect of the rotation model on blended learning stations on the achievement of third-grade female students. To verify the goal of the research, the null hypothesis was developed, which states: there is no statistically significant difference at the significance level (0.05) between the average scores of the female students in the experimental group who studied using the rotation model on the blended learning stations and the scores of the female students in the control group who studied using the traditional method in the achievement test. The researchers adopted an experimental design of two equal groups (the experimental group and the control group) with a post-test. The experiment was applied to a sample of third-grade female students, numbering 60 female students, 29 female students in the experimental group, and 31 female students in the control group for the academic year 2023–2024. They were tested based on the mathematical information test, previous achievement in mathematics, and intelligence. The research tool was developed by researchers, represented by the achievement test. The experimental group was taught according to the model of alternating between blended learning stations, and the control group was taught according to the traditional method. After completing the experiment, the research tool was applied to both groups. Using the Statistical Portfolio for the Social Sciences (SPSS-V28), the results showed that the female students of the experimental group who were taught according to the rotation model in the blended learning stations outperformed the female students of the control group who were taught according to the traditional method in the academic achievement variable. Based on the results and their interpretation, the two researchers concluded that teaching female students according to the rotation model on blended learning stations contributed to increasing the achievement of the female students in the experimental research sample in mathematics. The model also worked to increase the motivation of the experimental group students towards the academic subject. In addition to finding bridges to link the scientific material's content with the previous experiences of the students, the research came up with a set of recommendations and suggestions